Menurunkan Kecanduan Game Dengan Penerapan Peraturan Penggunaan Ponsel Selama Pembelajaran Online - Yeni Elviani; Ira Kusumawaty; Yunike (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
The Covid-19 pandemic with restrictions to bemade, makes students familiar with mobile phones. Mobile phones are not only a medium of learning, but also as a very wide source of information and there are many other features including games. Without the proper application of mobile phone usage rules from parents and the environment, gaming will be a problem in the child's development. The study found a link between applying mobile phone use rules in online learning to gaming addiction in elementary school students. The behavior of applying mobile phone use regulations and gaming addiction is assessed through an online survey using quiziz to elementary school students in South Sumatra Province. The Chi-Square test is used to assess the significance of the results obtained. It was found that only a small percentage of mobile phone usage rules are applied to children, parents still give freedom to children to be familiar with mobile phones especially since online learning. This is exacerbated by a lack of mentoring and monitoring of mobile phone use. Intense interaction with mobile phones in children raises the issue of gaming addiction. more than half of the students who were respondents were indicated to be mildly addicted and a small number were indicated to be severe. The government applies online learning rules to an indefinite time limit so that a child's continuous exposure to a mobile phone is inevitable. It takes synergy between government, teachers and parents in assisting students in learning, tackling the game addiction that has occurred, and modifying the online learning system and thinking about the possibility of offline learning that applies health protocols so that students' education touch needs are met.